An Efficient Parametric Model-based Framework for Recursive Frequency/Spectrum Estimation of Nonstationary Signal - MVV Prasad, Kantipudi; H.N. Suresh, Dr.; Aluvalu, Rajanikanth (International Journal of Engineering and Technology, 2018)
The manuscript intends to a design a general form of computationally efficient parametric mechanism based model to estimate the recursive frequency/spectrum and describe the nonlinear signals which consists of diverse degrees of nonlinearity and and indiscreet units. The time variant frequency estimation is defined as the as a time-varying model recognizable proof issue in which faulty/failure data are evaluated by model coefficients. In this, anestimation approach of QR-disintegration based recursive slightest M-gauge (QRRLM) is utilized for estimation of recursive time-vareint model coefficients in non-linear environment conditionby utilizing M-estimation. Here, a Veriable Forgetting Factor Control (VFFC) are designed to enhance the exection of QRRLM mechanism in nonlinear condition. In this, a hypothetical deduction and re-enactments approaches were used which helps to perform VFFC determination. The resultant VFFC-QRRLM estimation can confine and limit the faulty unitswhile dealing with different degrees of nonlinearvariations. Recreation comes about demonstrate that the proposed VFF-QRRLM calculation is more vigorous and exact than traditional recursive minimum squares-based techniques in evaluating both time-shifting narrowband recurrence segments and broadband otherworldly segments with incautious parts. Potential uses of the proposed technique can be found in quality force checking, online deficiency location, and discourse examination.Â